In vivo analysis of the effect of panobinostat on cell-associated HIV RNA and DNA levels and latent HIV infection. Issue 1 (December 2016) - Tsai, Perry; Wu, Guoxin; Baker, Caroline; Thayer, William; Spagnuolo, Rae; Sanchez, Rosa; Barrett, Stephanie; Howell, Bonnie; Margolis, David; Hazuda, Daria; Archin, Nancie; Garcia, J.
Abstract Background The latent reservoir in resting CD4+ T cells presents a major barrier to HIV cure. Latency-reversing agents are therefore being developed with the ultimate goal of disrupting the latent state, resulting in induction of HIV expression and clearance of infected cells. Histone deacetylase inhibitors (HDACi) have received a significant amount of attention for their potential as latency-reversing agents. Results Here, we have investigated the in vitro and systemic in vivo effect of panobinostat, a clinically relevant HDACi, on HIV latency. We showed that panobinostat induces histone acetylation in human PBMCs. Further, we showed that panobinostat induced HIV RNA expression and allowed the outgrowth of replication-competent virus ex vivo from resting CD4+ T cells of HIV-infected patients on suppressive antiretroviral therapy (ART). Next, we demonstrated that panobinostat induced systemic histone acetylation in vivo in the tissues of BLT humanized mice. Finally, in HIV-infected, ART-suppressed BLT mice, we evaluated the effect of panobinostat on systemic cell-associated HIV RNA and DNA levels and the total frequency of latently infected resting CD4+ T cells. Our data indicate that panobinostat treatment resulted in systemic increases in cellular levels of histone acetylation, a key biomarker for in vivo activity. However, panobinostat did not affect the levels of cell-associated HIV RNA, HIV DNA, or latently infected resting CD4+ T cells. Conclusion We have demonstrated robust levels of systemic histone acetylation after panobinostat treatment of BLT humanized mice; and we did not observe a detectable change in the levels of cell-associated HIV RNA, HIV DNA, or latently infected resting CD4+ T cells in HIV-infected, ART-suppressed BLT mice. These results are consistent with the modest effects noted in vitro and suggest that combination therapies may be necessary to reverse latency and enable clearance. Animal models will contribute to the progress towards an HIV cure.